HUBUNGAN STATUS KESEHATAN GIGI DAN MULUT DENGAN PRESTASI BELAJAR SISWA/I SD NEGERI 2 SANGGA BERU KECAMATAN GUNUNG MERIAH KABUPATEN ACEH SINGKIL - Nurhamidah Nurhamidah; Ety Sofia Ramadhan; Asmawati Asmawati; Juni Juni (Jurnal Kesehatan Gigi, 2016)
TITLEThe relationship between oral hygiene status and learning achievement of students in SD Negeri 2 Sangga Beru, Gunung Meriah, Aceh SingkilABSTRACTDental and oral health is art of physical health which cannot be separated from one to each other. The main problem is that many school children are affected by caries which can decrease their learning ability. The objective of the research was to find out the correlation between dental and oral health status and elementary school students’ learning performance.The research used analytic descriptive method with cross sectional study design. The samples were 70 elementary school students, taken by using random sampling technique. Primary data were gathered by conducting clinical examination and secondary data by finding out progress report cards. The gathered data were analyzed by using bivatriate analysis with chi square statistic test.The result of the research showed that 50% of the respondents had good dental and health status (def-t and DMF-T), 32.9% of them had moderate def-t and DMF-T, and 17.1% of them had bad def-t and DMF-T. It was also found that 42.9% of the respondents had bad learning performance, 38.6% of them had moderate learning performance, and 18.6% of them had good learning performance. The result of chi square test showed that there was significant correlation between dental and oral health status and students’ learning performance at SDN 2 Sangga Beru, Gunung Meriah Subdistrict, Aceh Singkil District at p-value = 0.009 (p ≤ 0.05). The conclusion of the research was that dental and oral health status could influence learning performance.Key words : Dental and Oral Health Status, Learning Performance